2011
DOI: 10.1099/jmm.0.031062-0
|View full text |Cite
|
Sign up to set email alerts
|

New types of toxin A-negative, toxin B-positive strains among clinical isolates of Clostridium difficile in Australia

Abstract: A total of 817 human clinical isolates of Clostridium difficile from all Australian states were screened for A " B + strains by toxin gene PCR assays. Nine (1.1 %) strains were confirmed to be A " B + by enzyme immunoassay for toxin production. Of these, six (66.7 %) were binary toxinpositive by PCR. Using PCR ribotyping and toxinotyping, the A "

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…Toxinotypes XXIII and XXIV were briefly described as new types (24), and types XXV to XXIX and types XXXIII and XXXIV were not included in any previous publication and are described here for the first time. Two new A Ϫ B ϩ toxinotypes from Australia, XXX and XXXI, have been reported (25), while another A Ϫ B ϩ toxinotype, XXXII, was published recently as the only known strain with a PaLoc located outside the usual chromosomal integration site (8). …”
Section: Overview Of Known Toxinotypesmentioning
confidence: 99%
“…Toxinotypes XXIII and XXIV were briefly described as new types (24), and types XXV to XXIX and types XXXIII and XXXIV were not included in any previous publication and are described here for the first time. Two new A Ϫ B ϩ toxinotypes from Australia, XXX and XXXI, have been reported (25), while another A Ϫ B ϩ toxinotype, XXXII, was published recently as the only known strain with a PaLoc located outside the usual chromosomal integration site (8). …”
Section: Overview Of Known Toxinotypesmentioning
confidence: 99%
“…The main virulence factors of C. difficile are C. difficile toxin A (TcdA) and C. difficile toxin B (TcdB), which are encoded by the genes tcdA and tcdB, respectively (3,4). In addition, a separate binary toxin is produced by a small group of isolates with or without TcdA and/or TcdB (5,6), and it has been suggested that the binary toxin may play a part in the recurrence of C. difficile infection (CDI) (7). As the role of the binary toxin in CDI currently is not well understood, it has not become a common target for diagnostic assays.…”
mentioning
confidence: 99%
“…This resulted in a specificity of 97% and a subsequent PPV of 51%, while remaining the high sensitivity of 95.8%. However, in the rare event a patient is colonized with a toxin A-negative, toxin B-positive C. difficile strain (26,27), the new strategy will not identify this strain. The test results of artus PCR showed lower inhibition rates than the in-house PCR, at 8% versus 5.3%, respectively; however, inhibition of the in-house PCR was overcome by adding the PCR enhancer BSA (28).…”
Section: Discussionmentioning
confidence: 99%
“…For CDI diagnosis, the use of a two-step algorithm is recommended (27). After a first sensitive test, which reliably classifies nondiseased patients, a more specific test is applied as a second test to discern true positives from false positives.…”
Section: Discussionmentioning
confidence: 99%